Structural Equation Modeling to Analyze Person-Organization Fit and Organizational Effectiveness - Hadi Teimouri; Kouroush Jenab; Somaye Rafei; Maryam Yonespoor (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Efficient management and leadership can be achieved via precise planning for selection, recruitment, and optimization of the labor force. One of the major goals in labor force selection and recruitment is the fit between people and an organization. This phenomenon is known as person-individual fit. In this research, the authors collected data via a survey aimed at exploring the relationship between person-individual fit and organizational effectiveness at the University of Isfahan. The research hypotheses were tested through variables such as environmental congruence, KSA (knowledge/skills/abilities) congruence, goals congruence, values congruence, and personality congruence, as dimensions of person-individual fit. The aim of this study is developing and practical and from the procedure implemented is introducing-analyzing. The sample studied in this study is the mangers and employers of the university in Isfahan. A stratified random sampling method was used based the Morgan table and a sample size of 120 was chosen from among 150 persons. The results revealed that there is a significant relationship between dimensions of person-individual fit and organizational effectiveness.